Organocatalytic asymmetric Henry reaction of 1H-pyrrole-2,3-diones with bifunctional amine-thiourea catalysts bearing multiple hydrogen-bond donors - Zhang, Ming-Liang; Yue, Deng-Feng; Wang, Zhen-Hua; Luo, Yuan; Xu, Xiao-Ying; Zhang, Xiao-Mei; Yuan, Wei-Cheng (Beilstein Journal of Organic Chemistry, 2016)
For the first time, a catalytic asymmetric Henry reaction of 1H-pyrrole-2,3-diones was achieved with a chiral bifunctional amine-thiourea as a catalyst possessing multiple hydrogen-bond donors. With this developed method, a range of 3-hydroxy-3-nitromethyl-1H-pyrrol-2(3H)-ones bearing quaternary stereocenters were obtained in acceptable yield (up to 75%) and enantioselectivity (up to 73% ee).
Keywords: asymmetric catalysis; bifunctional catalysts; Henry reaction; organocatalysis; 1H-pyrrole-2,3-diones